Analisis Relasional Hukum Negara dan Hukum Rakyat dalam Konflik Agraria Bongkoran, Kabupaten Banyuwangi, Jawa Timur, Indonesia - Umar Sholahudin; Hotman Siahaan; Herlambang Perdana Wiratraman (Society, 2020)
Apart from having a socio-economic dimension, agrarian conflicts in Bongkoran, Banyuwangi Regency, East Java Province, Indonesia, also have a legal dimension. There is a dualism of law that is conflictual in terms of land tenure and use claims. One party, the government, and corporations rely on legalistic-positivistic state laws, while local people rely on folk law, namely informal laws that have existed, lived, and developed in communal society for generations. This research focuses on how the sociological perspective of law analyzes the legal conflicts that occur in Bongkoran agrarian conflict, particularly between state law and folk law. This research used a qualitative method with a legal sociology perspective. The research subjects were farmers/people of Bongkoran, Community Legal Advisors (CLA), Government (Local Government, National Land Agency, and Police), and corporate elements (PT Wongsorejo). Informants were selected using a purposive sampling technique, based on certain considerations that can be recognized beforehand, namely recognizing and understanding the problem under this research. Data collection was conducted through observation, in-depth interviews, and documentation. The collected data were analyzed qualitatively by referring to the perspectives that have been presented. The results indicated that the resolution of agrarian conflicts in Bongkoran requires the implementation of laws that are more just for local communities. The implementation of the laws is not only based on rigid articles in the law, but it needs attention to the socio-cultural and historical context of the community. The dominance of state law over folk law in agrarian conflicts results in the practice of subjugation of state law to folk law, both persuasively and repressively. Therefore, to minimize the tension and conflict between state law and folk law in agrarian conflicts, it is necessary to have a new understanding of the relationship between the two laws. The existence and enforcement of folk law are used as a complementary element in normative aspects that have not been regulated in state law.